Factors associated with food choice motives of adolescents in Yogyakarta Special District - Rifka Wahyuningtyas; Setyo Utami Wisnusanti; Mutiara Tirta Prabandari Lintang Kusuma (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2021)
Background: Adolescents begin to have eating autonomy which causes changes in behavior and habits related to food selection. Various factors are considered to be able to influence food choice motives. Objective: The study aimed to determine factors related to adolescents' food choice motives. Methods: A cross-sectional study involving 121 students who studied at two state Junior High schools in Yogyakarta Special District (YSD) from April to May 2020. The independent variables are gender, perception of body image, nutritional knowledge, peer influence, school location, amount of pocket money, family income, parental education, and media influence. The dependent variables are nine food choice motives. Data collection was used online questionnaires via an online form. The data were analyzed by using multiple linear regression. Results: Most respondents had health motive as their primary motive in food choice, followed by natural content, price, and ethical concern. This research also found that there was a relationship between nutritional knowledge with a natural content motive; media influence, nutritional knowledge, and amount of pocket money with ethical concern motive; parental education with price motive; perception of body image, media influence, amount of pocket money, and nutritional knowledge with weight control motive (p<0,05). Conclusions: Perception of body image, nutritional knowledge, media influence, amount of pocket money, and parental education were related to the food choice motives of adolescents. Future intervention strategies related to healthy eating behavior in adolescents can be designed based on these factors.* Presented at the International Nutrition and Health Symposium (INHESION) on Sunday, November 15th, 2020, in Yogyakarta, organized by HIMAGIKA and the Department of Health Nutrition, Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada